2011
DOI: 10.1159/000334214
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Repeat Thyroid Fine-Needle Aspiration in the Management of Thyroid Nodules

Abstract: Objective: The Bethesda System for reporting thyroid fine-needle aspirations (FNAs) recommends repeat aspirations be done at least 3 months following the initial aspiration to prevent false-positive misinterpretations due to reactive/reparative changes. Because limited data exists, we reviewed our own data to ascertain the recommendation. Study Design: We retrospectively reviewed thyroid FNAs accessioned in the Cytology Laboratory at Beth Israel Deaconess Medical Center in Boston, Mass., USA, from January 2006… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 11 publications
7
32
2
1
Order By: Relevance
“…It is well known and demonstrated by others that a repeat FNA for nondiagnostic aspirates is of benefit where some cases may show malignancy. Similar to our previous study and other investigators, a repeat FNA with a more appropriate triage is of significant benefit in many of these cases [13,16,17,18,19,20]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is well known and demonstrated by others that a repeat FNA for nondiagnostic aspirates is of benefit where some cases may show malignancy. Similar to our previous study and other investigators, a repeat FNA with a more appropriate triage is of significant benefit in many of these cases [13,16,17,18,19,20]. …”
Section: Discussionsupporting
confidence: 87%
“…This rate is relatively comparable to other studies [16,17,18,19,20,21,22]. Out of those 25, 4 had a subsequent surgical follow-up where 1 (25%) revealed papillary thyroid carcinoma and the other 3 (75%) resulted in a benign surgical diagnosis.…”
Section: Discussionsupporting
confidence: 84%
“…This is what has led to a wait of at least 3 months before the next biopsy is performed. Several recent studies have reported that the timing of repeat FNAB does not influence the atypical cytology results [7,8,9]. A case series of 298 patients with ND results reported no significant difference between the AUS/FLUS results of repeat FNAB of an earlier (<3 months) and a later (≥ 3 months) biopsy group [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported that repeat FNAB performed within 3 months did not increase the atypical cytologic results [7,8,9]. According to the Bethesda System for Reporting Thyroid Cytopathology, the category follicular lesion of undetermined significance (FLUS)/atypia with undetermined significance (AUS) includes cases which do not have convincing evidence of benignity or sufficient features in order to conclude that they are follicular neoplasms or suspicious for malignancy [1].…”
Section: Introductionmentioning
confidence: 99%
“…The ROM was 2-4% among all initially ND samples and 9-32% among those ND samples that were resected [4]. While it was originally recommended to wait >3 months to perform a repeat FNA, evidence exists to support shorter intervals for repeating an FNA after a ND result [4,19,20]. However, it should be noted that reactive atypia and other cellular changes may be present if the time interval is shortened.…”
Section: Specific Issues Pertaining To the Different Diagnostic Categmentioning
confidence: 99%